Hans Christian Andersen's fairy tales - Parker, Vic; Andersen, Hans Christian 1805-1875 (Essex : Miles Kelly., 2017)
The fairy tales of Hans Christian Andersen have inspired, frightened, and amused readers since they were first published in 1835. Readers will recognize the little mermaid who makes a deal with a sea witch in the hopes of winning a prince's heart; the conceited emperor who is swindled by two men who claim to be weaving magical cloth, and many more. There are 39 total stories in this volume.
U
b
b
Keywords: fairy tales